Effect of Clozapine on Anti-N-Methyl-D-Aspartate Receptor Encephalitis With Psychiatric Symptoms: A Series of Three Cases - Yang, Ping; Li, Liang; Xia, Shuaishuai; Zhou, Bin; Zhu, Yong; Zhou, Gaoya; Tu, Erwen; Huang, Tianhao; Huang, Huiyong; Li, Feng (Frontiers in Neuroscience, 2019)
The main clinical manifestations of anti-NMDA receptor (NMDAR) encephalitis are acute or subacute seizures, cognition impairment and psychiatric symptoms. Nowadays, the scheme of antipsychotic therapy for this disease has not been established. This study reports three cases of anti-NMDAR encephalitis with psychiatric symptoms. The anti-NMDAR antibodies in cerebrospinal fluid (CSF) and serum were positive. The psychiatric symptoms still existed after the treatment of intravenous immunoglobulin (IVIG), so clozapine was used for antipsychotic therapy. Case 1 was a 37-year-old man who suffered from bad mood and suicide behaviors for 1 month. Hallucination and delusion still existed after the treatment of IVIG and hormone therapy, and the symptoms were relieved when given clozapine for 12 months. Case 2 was a 28-year-old man who was admitted to our hospital due to injuring other people and destructive behaviors for 2 days. He showed irritability, bad temper, declined cognition and severe delusion of persecution after the treatment of IVIG and hormone, but the psychiatric symptoms disappeared when given clozapine for 3 months. Case 3 was a 23-year-old man who suffered from headache and babbing for 7 days. The symptoms of irritability, bad temper, babbing and injuring other people still existed after the treatment of IVIG and hormone therapy, but they disappeared when given clozapine for 2 months. Therefore, we suggest that during the treatment of anti-NMDAR encephalitis with psychiatric symptoms, if the anti-NMDAR antibodies in CSF and serum were positive, and psychiatric symptoms could not be controlled after IVIG and hormone therapy, clozapine may work.